Peoples, nature and environments : learning to live together - Roque, Ana Cristina; Brito, Cristina; Veracini, Cecilia (Cambridge Scholars Publishing, 2020)
This volume brings together perspectives from scholars of different scientific backgrounds endeavouring to understand and debate the interactions and relationships between humans, nonhuman species and natural ecosystems in order to overcome the classic human/environment dichotomy. Through discussions informed by the humanities, arts, social and natural sciences, the book deals with the way different disciplines approach this relationship. These diverse perspectives are compared to enable a cross-cutting analysis of human/nature interface throughout history. Changes forced by the utilization of.